2017
DOI: 10.1002/path.4995
|View full text |Cite
|
Sign up to set email alerts
|

Synaptopodin‐2 suppresses metastasis of triple‐negative breast cancer via inhibition of YAP/TAZ activity

Abstract: Triple-negative breast cancer (TNBC) represents the most aggressive subtype of breast cancer, with a high incidence of distant metastasis; however, the underlying mechanism for this frequent recurrence remains unclear. Herein, we show that synaptopodin-2 (SYNPO2), a putative tumour suppressor in aggressive cancer, is frequently downregulated in TNBC by methylation of the promoter of SYNPO2. Low expression levels of SYNPO2 correlated significantly with 5-year metastatic relapse, and predicted poorer prognosis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 59 publications
2
33
0
Order By: Relevance
“…Another study published at that time also found that activation of YAP, in this case through loss of Leukemia Inhibitory Factor Receptor (LIFR), promoted metastatic colonization of breast cancer cells [ 117 ]. Since these initial studies, several others have directly implicated YAP, TAZ, or TEADs in metastasis of numerous cancer types, including melanoma [ 118 ], lung cancer [ 119 , 120 , 121 ], breast cancer [ 86 , 122 , 123 , 124 , 125 , 126 , 127 , 128 ], cholangiocarcinoma [ 82 , 129 ], gastric cancer [ 130 , 131 , 132 , 133 ], ovarian cancer [ 134 ], colorectal cancer [ 135 , 136 , 137 ], and oral squamous cell carcinoma [ 101 ]. Conversely, LATS1 overexpression reduces gastric cancer metastasis [ 138 ].…”
Section: Yap/taz-tead Drives Cancer Formation Tumor Growth and Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study published at that time also found that activation of YAP, in this case through loss of Leukemia Inhibitory Factor Receptor (LIFR), promoted metastatic colonization of breast cancer cells [ 117 ]. Since these initial studies, several others have directly implicated YAP, TAZ, or TEADs in metastasis of numerous cancer types, including melanoma [ 118 ], lung cancer [ 119 , 120 , 121 ], breast cancer [ 86 , 122 , 123 , 124 , 125 , 126 , 127 , 128 ], cholangiocarcinoma [ 82 , 129 ], gastric cancer [ 130 , 131 , 132 , 133 ], ovarian cancer [ 134 ], colorectal cancer [ 135 , 136 , 137 ], and oral squamous cell carcinoma [ 101 ]. Conversely, LATS1 overexpression reduces gastric cancer metastasis [ 138 ].…”
Section: Yap/taz-tead Drives Cancer Formation Tumor Growth and Mmentioning
confidence: 99%
“…As with EMT, YAP/TAZ-mediated migration and invasion is dependent upon TEADs. Importantly, several studies that demonstrate YAP or TAZ-dependent metastasis formation also showed that YAP or TAZ promotes the migration and/or invasion of the cancer cells [ 82 , 86 , 118 , 120 , 125 , 128 , 129 , 132 , 133 , 135 , 136 , 137 ]. Although the YAP/TAZ target genes responsible for enhanced tumor cell migration and invasion are likely numerous, context-dependent, and cancer-type specific, some have been clearly identified.…”
Section: Yap/taz-tead Drives Cancer Formation Tumor Growth and Mmentioning
confidence: 99%
“…leading to YAP cytoplasmic retention and degradation. YAP S127A , an activated mutant, 24 was constructed to avoid LATS1 inhibition and enhance CCN2-promoter activity ( Figure S7). Our result showed that Gas6 increased CCN2-promoter activities in Vector groups and YAP WT groups.…”
Section: Axl Promotes Yap Nuclear Translocation and Transcriptionalmentioning
confidence: 99%
“…Both proteins are key players in the Hippo pathway and have known functions in metastasis formation, consistently with the changes we observed in cultured TNBC cells and xenografts after vitamin C treatment. Activation of YAP1 promotes F-actin assembly and lamellipodia formation, which are essential to cell mobility and invasion [19]. Our results show that vitamin C treatment downregulates the expression of YAP1 and upregulates that of SYNPO2, which further inhibits the activity of YAP1.…”
Section: Discussionmentioning
confidence: 66%
“…SYNPO2 has been found to suppress metastasis by inhibiting the activity of the transcriptional coactivator YAP1, also known as yes-associated protein 1 [19]. As a key regulator in the Hippo pathway, YAP1 promotes focal adhesion formation and metastasis [20].…”
Section: Vitamin C Decreases Yap1 Expression In Tnbc Cellsmentioning
confidence: 99%